2008
DOI: 10.1007/s00264-008-0689-6
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of magnetic resonance imaging in acute multi-ligament injuries

Abstract: This study compares MRI with examination under anaesthesia to surgical findings in evaluating soft tissue injuries in acute multi-ligament knee trauma. Preoperative MRI was done for 44 patients who underwent surgery for grade III ACL and grade III medial collateral ligament (MCL) injury. In 21 cases both ACL and MCL were treated surgically, but in 23 only ACL. Intra-operative and MRI findings were compared. Accuracy of MRI for medial meniscal tears was 88.6%, sensitivity 80%, and specificity 91.2%; accuracy fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 18 publications
3
45
0
1
Order By: Relevance
“…[20] Table 2 summarizes the bone bruise prevalence and location in all but three studies that reported bone bruise prevalence in specifically the lateral and/or medial compartments of the tibia and femur. [2123] The three studies were not included in Table 2 because they only reported bone bruise prevalence within the anterior, posterior, and/or middle aspects of the lateral and medial compartments of the tibia and femur. The studies were included in Table 3 and their bone bruise data was compared to other studies that also analyzed bone bruise prevalence within the specific anterior, middle, and/or posterior aspects of the lateral and medial compartments.…”
Section: Resultsmentioning
confidence: 99%
“…[20] Table 2 summarizes the bone bruise prevalence and location in all but three studies that reported bone bruise prevalence in specifically the lateral and/or medial compartments of the tibia and femur. [2123] The three studies were not included in Table 2 because they only reported bone bruise prevalence within the anterior, posterior, and/or middle aspects of the lateral and medial compartments of the tibia and femur. The studies were included in Table 3 and their bone bruise data was compared to other studies that also analyzed bone bruise prevalence within the specific anterior, middle, and/or posterior aspects of the lateral and medial compartments.…”
Section: Resultsmentioning
confidence: 99%
“…[67] In a study which performed in our country, the authors found highest sensitivity, specificity, and accuracy in MRI for LM injuries. [2] In another study performed by Halinen et al ., they showed that the sensitivity was higher in MM injuries and specificity was higher in LM injuries.…”
Section: Discussionmentioning
confidence: 99%
“…[2] In another study performed by Halinen et al ., they showed that the sensitivity was higher in MM injuries and specificity was higher in LM injuries. [7]…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Halinen et al, 2008 (19) referred to the Causes of false MRI interpretations as many, including technical and anatomy-related causes. Some errors in the MRI interpretation may be related to problems in the use of arthroscopic findings as the standard of reference, including lack of imaging of some tears under the surface of the posterior horn, reliance on probing or compression to diagnose tears, and differences in descriptive terminology for disease of or damage to the meniscus .…”
Section: Discussionmentioning
confidence: 99%